The clinical course and multidisciplinary management of an in-hospital ruptured mycotic abdominal aortic aneurysm - Margarita Pipinos, BS; Kelly Cawcutt, MD; Alexandra Sorrick, MD; Jonathan Thompson, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Mycotic aneurysms are rare, accounting for 1% to 3% of all arterial aneurysms; nevertheless, they are associated with significant morbidity and mortality. We present the case of a 55-year-old man with severe abdominal pain, fevers, and night sweats. Rapid clinical deterioration, alongside blood cultures significant for methicillin-susceptible Staphylococcus aureus bacteremia led to imaging revealing a ruptured and infected abdominal aortic aneurysm, necessitating emergent endovascular repair and intravenous antibiotic therapy. This case report explores the diagnostic challenges of identifying mycotic aneurysms, underscores the importance of early multidisciplinary intervention, and emphasizes the necessity of long-term antimicrobial therapy to prevent graft reinfection.